System reliability analysis of geosynthetic reinforced soil slope considering local reinforcement failure. (July 2020) - Peng, Ming; Sun, Rui; Chen, Jian-Feng; Rajesh, Sathiyamoorthy; Zhang, Li-Min; Yu, Song-Bo
Abstract: System reliability analyses are necessary for geosynthetic reinforced soil slopes because of the uncertainties associated with design parameters and complicated interaction between geosynthetic reinforcements and soil. This paper presents a new method for system reliability analysis of reinforced soil slopes considering local failures of reinforcements based on total probability rule with a typical example. The slope failure probability is calculated as the sum of the products of the local reinforcement failure probability and the conditional probability of the slope failure given the local reinforcement failure. An event tree is used to evaluate all possible mutually exclusive local reinforcement failure combinations. The present method avoids the assumption of different independent failure modes and is able to take the composite failure mode into account. The failure of local reinforcements incurs the redistribution of the forces in the other layers and increases the failure probability of the adjacent upper reinforcement layers, leading to cascading failure one after another. The failure probability of a reinforced slope is determined by both the probability of the local reinforcement failures and conditional probability of the slope given those events. It is not necessary to set the correlation coefficient between different failure modes in the present method.